SLC7A11/ xCT is a target of miR-5096 and its restoration partially rescues miR-5096-mediated ferroptosis and anti-tumor effects in human breast cancer cells. (1st December 2021) - Yadav, Poonam; Sharma, Priyanshu; Sundaram, Sandhya; Venkatraman, Ganesh; Bera, Amal Kanti; Karunagaran, Devarajan
Abstract: Breast cancer cells evade cell death by overexpressing SLC7A11, which functions by transporting cystine into cells in exchange for intracellular glutamate facilitating glutathione synthesis and reducing reactive oxygen species (ROS)–mediated stress. Using an in silico approach, we predicted an miRNA (miR-5096) that can target and downregulate SLC7A11. We demonstrated SLC7A11 as a target of miR-5096 by 3′UTR luciferase assay and further validated it by identifying reduced mRNA and protein levels of SLC7A11 upon miR-5096 overexpression. miR-5096–induced ferroptotic cell death in human breast cancer cells was confirmed by concurrently increased ROS, OH −, lipid ROS, and iron accumulation levels and decreased GSH and mitochondrial membrane potential (MitoTracker™ Orange) with mitochondrial shrinkage and partial cristae loss (observed by TEM). miR-5096 inhibited colony formation, transwell migration, and breast cancer cell invasion, whereas antimiR-5096 promoted these tumorigenic properties. Ectopic expression of SLC7A11 partly reversed miR-5096-mediated effects on cell survival, ROS, lipid peroxides, iron accumulation, GSH, hydroxyl radicals, mitochondrial membrane potential, and colony formation. miR-5096 modulated the expression of epithelial-mesenchymal transition markers in vitro and inhibited the metastatic potential of MDA-MB-231 cells in a tumor xenograft model of zebrafish larvae. Our results demonstrate that miR-5096 is a tumor-suppressive miRNA in breast cancer cells, and this paper discusses its therapeutic implications. Highlights: miR-5096 expression is lower and that of SLC7A11 is higher in human breast cancer cells and tissues compared to a non-tumorigenic epithelial cell line or adjacent normal tissues. SLC7A11 overexpression correlates with poor patient survival in breast cancer. mir-5096 targets and downregulates SLC7A11 and induces ferroptosis in breast cancer cells. miR-5096 suppresses proliferation, colony formation, migration and invasion of breast cancer cells. miR-5096 inhibits metastatic potential of MDA-MB-231 cells in vivo in zebrafish tumor xenograft model.